PENGUKURAN PERUBAHAN SUDUT POLARISASI OLEH FLUORESENSI PADA SAMPEL MINYAK ZAITUN - Nyadaniati Simbolon; Ketut Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
The aim of this research is to show how the quality difference of cooking oil affect polarization angle changes of fluorescence. The fluorescence could be usefull to identify quality of matter according to colour changes. In this research, to identify fluoresence polarization changes edible and expired olive oil used as sample with different expired date. To produce fluorescence, a green laser with wavelength 532 nm pass by polarizer and produce polarized light. Analizer sets perpendicular to polarization plane. The result show that quality difference affect the fluorescence polarization changes. The worst quality of oil the higher polarization changes. Smallest polarization changes we get in the best quality edible olive oil as 50,90 and 61,60 for the expired one.